Transformations of Aromatic Compounds by Nitrosomonas europaea - Keener, William K. (1994)
Benzene and a variety of substituted benzenes inhibited ammonia oxidation by intact cells of Nitrosomonas europaea. In most cases, the inhibition was accompanied by transformation of the aromatic compound to a more oxidized product or products. All products detected were aromatic, and substituents were often oxidized but were not separated from the benzene ring. Most transformations were enhanced by (NH(4))(2)SO(4) (12.5 mM) and were prevented by C(2)H(2), a mechanism-based inactivator of ammonia monooxygenase (AMO). AMO catalyzed alkyl substituent hydroxylations, styrene epoxidation, ethylbenzene desaturation to styrene, and aniline oxidation to nitrobenzene (and unidentified products). Alkyl substituents were preferred oxidation sites, but the ring was also oxidized to produce phenolic compounds from benzene, ethylbenzene, halobenzenes, phenol, and nitrobenzene. No carboxylic acids were identified. Ethylbenzene was oxidized via styrene to two products common also to oxidation of styrene; production of styrene is suggestive of an electron transfer mechanism for AMO. Iodobenzene and 1,2-dichlorobenzene were oxidized slowly to halophenols; 1,4-dichlorobenzene was not transformed. No 2-halophenols were detected as products. Several hydroxymethyl (-CH(2)OH)-substituted aromatics and p-cresol were oxidized by C(2)H(2)-treated cells to the corresponding aldehydes, benzaldehyde was reduced to benzyl alcohol, and o-cresol and 2,5-dimethylphenol were not depleted.